Small mammals of Uzhanskyi National Park (Ukrainian Carpathians) and its vicinities: a preliminary analysis - Barkaszi, Z.; Koval, N. (Theriologia Ukrainica, 2019)
A preliminary analysis of species composition, abundance and habitat preferences of small mammals in the territory of Uzhansky National Nature Park and its vicinities was conducted. Since the creation of the park in 1999, detailed studies on small mammals have not been conducted in the area. Thus, the present research is a first attempt to clarify the species composition and some ecological features of small mammals in the region. In September–October 2017, trappings of small mammals were conducted by traditional methods using Hero traps and live traps. Five key habitats were investigated: ‘mixed forest’, ‘forest edge’, ‘windfall’, ‘meadow’, and ‘shrubs’. The total number of trap days was 705 during which 101 specimens of 7 species were collected. One species — M. agrestis — was recorded first in Uzhansky National Park. The part of females in the general sample was higher than the part of males (58.4 % vs. 41.6 %, respectively). Among the studied habitats, the highest species richness was revealed in ‘meadow’, where all 7 species occurred. The most abundant but, at the same time, the poorest habitats were ‘mixed forest’ (34.4 specimens / 100 trap-days, 2 species) and ‘forest edge’ (20.0 specimens, 2 species). Among the 7 species revealed in the park and its vicinities, only one is considered abundant (S. tauricus). According to Shannon and Simpson diversity indices, the highest species diversity was revealed in ‘meadow’ (H = 0.746, D = 4.741), ‘windfall’ (H = 0.436, D = 2.579), and ‘shrubs’ (H = 0.430, D = 2.528), while ‘mixed forest’ and ‘forest edge’ showed the lowest diversity. By the level of habitat preference, the most eurytopic species were S. tauricus and M. glareolus. The yellow-necked field mouse preferred ‘mixed forest’ the most (Fij = 0.57) and clearly avoided ‘meadow’ and waterside ‘shrubs’. The shrews (Sorex) and voles (Microtus) under conditions of Uzhansky Park were stenotopic species occurring only in ‘meadow’ (Fij = 1.00). Habitats having the highest level of species diversity deserve special conservation attention. The current revised taxonomic list of orders Soriciformes and Muriformes includes 14 species. The presence of 2 species previously mentioned for the region have not been confirmed yet by actual records.